Gremlin, a Bone Morphogenetic Protein Antagonist, Is a Crucial Angiogenic Factor in Pituitary Adenoma - Kenta Koketsu; Daizo Yoshida; Kyongsong Kim; Yudo Ishii; Shigeyuki Tahara; Akira Teramoto; Akio Morita (International Journal of Endocrinology)
Gremlin is an antagonist of bone morphogenetic protein (BMP) and a major driving force in skeletal modeling in the fetal stage. Several recent reports have shown that Gremlin is also involved in angiogenesis of lung cancer and diabetic retinopathy. The purpose of this study was to investigate the role of Gremlin in tumor angiogenesis in pituitary adenoma. Double fluorescence immunohistochemistry of Gremlin and CD34 was performed in pituitary adenoma tissues obtained during transsphenoidal surgery in 45 cases (7 PRLoma, 17 GHoma, 2 ACTHoma, and 2 TSHoma). Gremlin and microvascular density (MVD) were detected by double-immunofluorescence microscopy in CD34-positive vessels from tissue microarray analysis of 60 cases of pituitary adenomas (6 PRLoma, 23 GHoma, 22 NFoma, 5 ACTHoma, and 4 TSHoma). In tissue microarray analysis, MVD was significantly correlated with an increased Gremlin level (linear regression: P<0.005,  r2=0.4958). In contrast, Gremlin expression showed no correlation with tumor subtype or Knosp score. The high level of expression of Gremlin in pituitary adenoma tissue with many CD34-positive vessels and the strong coherence of these regions indicate that Gremlin is associated with angiogenesis in pituitary adenoma cells.